Predictors of psychological and physiological measures of graduate student health during COVID-19 - Marashi, Maryam; Heisz, Jennifer J. (Frontiers in Education, 2022)
Introduction: The COVID-19 pandemic brought on higher-than-normal levels of anxiety and depression, especially among graduate students whose academic trajectory was disrupted. However, not all graduate students were affected and therefore, it is important to identify potential protective factors. Method: We recruited 61 graduate students whose research was directly impacted by the pandemic and examined their change in academic stressors since the onset of the pandemic. Hierarchical regression analyses were used to evaluate how perceived academic stressors brought on by the COVID-19 pandemic impacted anxiety, depression, and heart rate variability (HRV), and whether physical activity and trait resiliency independently buffered against the effects of stress. Results: Graduate students who reported greater changes in academic stressors since the onset for the pandemic were more anxious and depressed. Moderate-intensity physical activity explained significant variance in anxiety whereas resiliency explained significant variance in both anxiety and depression. HRV was higher in males than females, aligning with sex differences in vulnerability to stress and mental illness. Conclusion: Overall, the results suggest that resiliency and physical activity may offer unique protection against symptoms of anxiety and depression in graduate students experiencing increased academic stress during COVID-19. Institutions of higher education should consider investing in programs that encourage physical activity and promote resiliency by teaching mindfulness, stress management, and cognitive behavioral approaches.